Pragmatics of Tense and Time in News: From canonical headlines to online news texts - Chovanec, Jan (Pragmatics & Beyond New Series, 2014)
This book provides the first comprehensive account of temporal deixis in English printed and online news texts. Linking the characteristic usage of tenses with the projection of deictic centres, it notes how conventional tenses, particularly in headlines, are affected by heteroglossia arising from various accessed voices. The resulting tense shifts are interpreted pragmatically as a conventional reader-oriented strategy that creates the impression of temporal co-presence. It is argued that since different tense choices systematically correlate with the three main textual segments of news texts, the function of tense needs to be viewed in a close connection with its local context. Traditional news texts are also contrasted with online news, particularly as far as the effect of hypertextuality on the coding of time is concerned. A two-level structural framework for the analysis of online news is proposed in order to account for their increased textual complexity. The book will be of interest to a wide range of scholars and students working in the fields of media pragmatics, discourse analysis and stylistics.
https://katalog.adlr.link/Record/76-EBC1825435